The Impact of Euthanasia on the Healthcare System: A Comparative Study Between Malaysia and the Netherlands - Muhammad Iz Taufik Muhd Nasruddin; Noorfajri Ismail (USIM Press, 2024)
Euthanasia is the intentional act of causing the death of a person who is suffering from a terminal illness, usually at their own request. It is a controversial topic, with strong arguments for and against it. This study compares the legal framework governing euthanasia and endoflife in Malaysia and the Netherlands, as well as the ethical considerations and principles in Shariah law related to end-of-life decisions and euthanasia in these two countries. It also examines the effects of euthanasia on patient care, including the provision of palliative care and end-of-life support services. In Malaysia, euthanasia is strictly prohibited. The Malaysian government's position is that euthanasia is a violation of the sanctity of life and that it could lead to abuse. In the Netherlands, euthanasia is legal under certain conditions, such as if the patient is terminally ill and experiencing unbearable suffering. The study found that the legalization of euthanasia could have both positive and negative effects on the provision of patient care. On the one hand, it could lead to an increase in the availability of resources for palliative care and end-of-life support services. On the other hand, it could lead to a decrease in the quality of care for patients who are not eligible for euthanasia. The study concludes that the debate over euthanasia is complex and there is no easy answer. It is important to consider all of the potential effects of euthanasia before making a decision about whether or not to legalize it. More research is needed to fully understand the effects of euthanasia on patients, families, and society as a whole.